Ironic effects of performance are worse for neurotics. (May 2016) - Barlow, Matthew; Woodman, Tim; Gorgulu, Recep; Voyzey, Rob
Abstract: Objectives: To conduct the first examination of neuroticism as a predictor of (1) the incidence of what Wegner (1989, 2009) terms ironic processes of mental control and (2) the precision of ironic performance errors under high- and low-anxiety conditions. Design: Across two studies we employed a repeated-measures design. Method: In a football penalty-shooting task (Study 1) and a dart-throwing (Study 2) task, under high-anxiety and low-anxiety conditions, participants gained maximum points for hitting a target zone and fewer points for hitting a designated non-ironic error zone. Additionally, we instructed participants to be particularly careful not to hit a designated ironic error zone, because such hits would score minimum points. Results: Across both studies within-subjects moderation analyses revealed a consistent moderating effect of neuroticism on the incidence of ironic errors in the high-anxiety condition. Specifically, when anxious, neurotics displayed a significant increase in ironic performance error and a significant decrease in target hits. Importantly, non-ironic error did not differ across anxiety conditions. Additionally, Study 2 results revealed that neuroticism moderated the precision of ironic errors when anxious. Specifically, when anxious, neurotics' ironic error zone hits were significantly farther from the target zone and significantly farther into the ironic error zone than their relatively emotionally stable counterparts' errors. Conclusion: We provide the first evidence that neuroticism moderates both the incidence and precision of ironic performance errors. These results will enable practitioners in coaching environments to make evidence-based predictions and interventions regarding which individuals are most prone to ironic performance breakdown when anxious. Highlights: Across two studies we examined Wegner's theory of ironic processes of mental control. We used ecologically valid performance tasks and ecologically valid performance stressors. We provide the first evidence that neuroticism moderates ironic performance error. Neuroticism moderates the incidence of ironic performance error when anxious. Neuroticism moderates the precision of irony of ironic error when anxious.